Languaging myths and realities : journeys of Chinese international students - Zhang-Wu, Qianqian (New perspectives on language and education ;, 2022)
"Drawing on a digital ethnography of Chinese international students' first semester languaging practices, this book examines how they use their multilingual and multi-modal communicative repertories to facilitate languaging across contexts, in order to suggest how universities might better serve the needs of international students"--